Transforming STEM Learning through PBL to Improve Computational Thinking Skills - Hasanah, Uswatun; Huda, Nuril (PT. Anagata Sembagi Education, 2025)
Transforming STEM education through Problem-Based Learning (PBL) has emerged as a central strategy for strengthening university students’ computational thinking (CT) skills in response to the challenges of the digital age and Industry 4.0. This study provides a comprehensive analysis of how PBL supports CT development within Indonesian higher education, particularly in relation to the Merdeka Belajar–Kampus Merdeka curriculum reforms. However, it remains unclear how PBL can be effectively implemented within STEM education to systematically optimize the development of students’ computational thinking. The core problem addressed in this study concerns the absence of a coherent pedagogical framework that integrates PBL-STEM to comprehensively foster key CT components. Accordingly, this study examines the extent to which the application of PBL strengthens university students’ computational thinking within the context of the Merdeka Belajar–Kampus Merdeka curriculum. Using a systematic literature review approach, the study synthesizes 35 peer-reviewed publications indexed in SINTA and Scopus from 2017 to 2024, along with relevant national and international education policy documents. The findings indicate that PBL effectively enhances the five core components of CT, namely problem decomposition, pattern recognition, abstraction, algorithmic design, and iterative evaluation. PBL also promotes students’ creativity, collaboration, and reflective reasoning in addressing real-world, technology-driven problems across STEM disciplines. Nevertheless, challenges persist, including lecturer readiness, disparities in digital infrastructure, and the limited availability of standardized CT assessment frameworks. The study underscores the importance of strengthening pedagogical capacity, improving digital learning ecosystems, and adopting process-oriented assessment models to ensure sustainable PBL-STEM implementation in higher education.